Ferromagnetic to spin glass cross over in (La,Tb)(2/3)Ca1/3MnO3 - Sankar, C. Raj; Vijayanand, S.; Joy, Pattayil Alias (Solid State Sciences, 2009)
In the series La2/3-xTbxCa1/3MnO3, it is known that the compositions are ferromagnetic for smaller values of x and show spin glass characteristics at larger values of x. Our studies on the magnetic properties of various compositions in the La2/3-xTbxCa1/3MnO3 series show that the cross over from ferromagnetic to spin glass region takes place above x approximate to 1/8. Also, a low temperature anomaly at 30 K, observed in the ac susceptibility curves, disappears for compositions above this critical value of x. A mixed phase region coexists in the narrow compositional range 0.1 <= x <= 0.125, indicating that the ferromagnetic to spin glass cross over is not abrupt. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ferromagnetism; Magnetic clusters; Manganites; perovskite; Spin glass